The feasibility and effectiveness of telenutrition for remote dietary consultation: a systematic review and meta-analysis protocol - Mohd Daud, Nur Liyana Hasnaa (Faculty of Medicine and Health Sciences, University Putra Malaysia, 2023)
Aims and Design: Telenutrition offers a potentially useful health improvement approach by providing patients with remote online dietary counselling and disease management services. This review protocol will examine how feasible and effective providing online dietary consultation could be through telenutrition. Data Sources: Adhering to the PRISMA-P, articles from the Cochrane Library, PubMed, Google Scholar, EBSCo, and Scopus databases will be searched using PICOS (population, intervention, comparator, outcome, and study design). Review Methods: The inclusion criteria will be an RCT study design and intervention involving telehealth and telenutrition services, published in English between 1997 and 2022 and in full-text form. The overall risk of bias will be assessed using the Risk of Bias tool developed by the Cochrane Collaboration and the RevMan 5.0 computer program. The latter will be utilised to conduct a meta-analysis. The chosen studies’ heterogeneity will be assessed using a random-effects model and the I2 statistic. Each intervention’s efficacy will be indicated through the statistical significance of the between-group difference (p-value <0.05). The quality of the methodology will be assessed by measuring the RCT design using the Jadad scale, while the evidence quality will be determined using the GRADE system. Results: This review protocol will summarise evidence regarding the feasibility and effectiveness of employing telenutrition for remote dietary consultation. Conference presentations and peer-reviewed journal publications will be how the findings are disseminated. Conclusion and impact: The findings may help to guide the effective implementation of remote dietary consultation services for patients. Trial Registration No: CRD42022340706